Engineering of epidermis skin grafts using electrospun nanofibrous gelatin/ polycaprolactone membranes - Duan, Huichuan (Dove Medical Press, 2013)
Skin engineering provides a new strategy for treating a wide variety of skin defects. In particular, electrospun nanofibrous membranes have been used as carriers for epidermis engineering. The aim of this study was to investigate the feasibility of a modified gelatin and polycaprolactone (GT/PCL) electrospun membrane for epidermis engineering. The biocompatibility of the membranes was evaluated by seeding HaCaT cells (human keratinocyte cell line) on the membrane and the mechanical properties of the membranes were determined with and without cells after culture. A cell proliferation assay showing that HaCaT cells attached and proliferated well on the membranes demonstrated that the membranes possess good biocompatibility. Mechanical tests showed that the membranes are strong enough to be handled during transplantation. Further in vivo transplantation studies revealed that epidermises engineered with GT/PCL membranes were able to repair skin defects in the nude mouse. These results demonstrate that GT/PCL electrospun membranes could be suitable scaffolds for skin engineering.